Strategy to Increase Employee Engagement Through Learning Agility and Organizational Citizenship Behavior in the National Defense Agency at the District Level - Hamdani, Maulana; Pratminingsih, Sri Astuti (IJSM, 2025)
This study aims to analyze the effect of learning agility on employee engagement with organizational citizenship behavior (OCB) as a mediating variable at the National Land Agency (BPN) in one of the districts in West Java Province. The research method used is descriptive verification with a quantitative approach, involving 65 employees as respondents through a saturated sampling technique. Data were collected using a structured questionnaire and analyzed using path analysis and the Sobel test to test the mediation effect. The results show that learning agility has a significant effect on employee engagement, both directly and indirectly through OCB as a mediator. The R Square value of 0.932 indicates that the combination of learning agility and OCB explains 93.2% of the variation in employee engagement. This finding emphasizes the importance of managerial strategies that encourage adaptive learning and strengthen organizational citizenship values in creating a productive, collaborative, and responsive work environment to change. This study provides a practical contribution to the development of public sector HR policies oriented towards increasing employee engagement through strengthening a learning-based and collaborative work culture